Tobin's Marginal q and Average q: A Neoclassical Interpretation - Hayashi, Fumio (Econometrica, 1982)
[It is increasingly recognized that Tobin's conjecture that investment is a function of marginal q is equivalent to the firm's optimal capital accumulation problem with adjustment costs. This paper formalizes this idea in a very general fashion and derives the optimal rate of investment as a function of marginal q adjusted for tax parameters. An exact relationship between marginal q and average q is also derived. Marginal q adjusted for tax parameters is then calculated from data on average q assuming the actual U.S. tax system concerning corporate tax rate and depreciation allowances.]